The popular commune and its institutions between the end of the thirteenth and the beginning of the fourteenth centuries. Some reflections starting from the historiography of the last fifteen years - Alma Poloni (Reti Medievali Rivista, 2012)
In recent years, the period between ca. 1280 and 1330 has attracted a growing interest among scholars who study Italian communes. As regards in particular the greatest popular communes, a specific attention to institutional dynamics has allowed to develop a complex model to explain the transformations of the late thirteenth and early fourteenth centuries. However, there remain some difficulties in understanding fully the nature of the political conflicts that marked that phase. Popolani and magnati, guelphs and ghibellines, popolo grasso and popolo minuto, bianchi and neri: urban communities were traversed by multiple and overlapping lines of fracture, in a process of decomposition and recomposition of political identities in which horizontal “class” solidarities, family solidarities, conflicts of interest, clientelist logics and ideological claims acted simultaneously. The article puts forward the idea that a better understanding of these conflicts, of their protagonists – groups, families, individuals – and their political and discursive strategies would improve our ability to read the institutional evolution of the popular communes between the end of the thirteenth and the beginning of the fourteenth centuries.